Electroluminescence from Plasmonic Excitations in a Scanning Tunnelling Microscope - Edelmann, Kevin (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2019)
This work presents the design and commissioning of a new low-temperature Scanning Tunnelling Microscope equipped with an innovative light collection setup using an integrated, micro-fabricated mirror tip. Commissioning experiments demonstrate the capabilities of this new instrument and reproduce known effects regarding gap plasmons on noble-metal surfaces. Furthermore, different contrasts in the plasmon-mediated light emission from Cobalt nano-islands on a Copper (111) substrate are reported.